Phenomenological understanding of subjectivity and its significance for psychology - Rosiychuk, Tetiana (Psyhology & society, 2019)
The article explores the basics of phenomenological program offered by Husserl to psychology. Actualization of the phenomenological approach matches with enlarging the natural science expansion to the sphere of the subjective. Once again this situation bringes up the class of problems that has been touched upon in two ideologically different works on the crisis in science by philosopher E. Husserl and psychologist L.S. Vygotsky. However, we believe that the evolution of Vygotsky’s view led him eventually to laying the foundations of the essentially phenomenological concept of the development of personality, which was not find a room in psychology. Guided by his discoveries, and based on the ideas of philosophers and psychologists of the phenomenological circle, we see an opportunity to elaboratethe speaking development concept on the basis of the main eventness moments in the development of subjectivity.